Situating Nutri-Ethics at the Junction of Nutrigenomics and Nutriproteomics in Postgenomics Medicine - Bragazzi, Nicola Luigi (Bentham Science Publishers, 2013)
Food has societal, economic, medical and ethical implications, being fundamental for life. It plays an important role also in sports medicine, since a healthy diet is an important part of an athlete's training. Nutrigenomics and nutriproteomics are emerging as a result of a convergence of nutritional, genomics and proteomics knowledge strands in the postgenomics era. These fields of inquiry present an opportunity for the design of customized diets potentially able to counterbalance the extant obesity epidemic and remedy metabolic diseases, among others. They are noteworthy for sport medicine as well since they could provide athletes with crucial information for personalized training and nutrition, in order to achieve the best results possible and express one's own potential. But they could also be used as a form of personalized doping, thus constituting an advancement of “classical nutrition-based doping” (i.e., the use of nutraceuticals, stimulants and supplements). However, nutrigenomics (or nutriproteomics)-based nutritional doping is different from the first-generation doping because it is specifically tailored to the genomics and proteomics makeup of the athlete, although their effectiveness remain to be discerned in future systematic studies. Against this scientific background, ethical issues of nutrigenomics and nutriproteomics are discussed in the present paper with emphasis on the current limitations and the dizzying potentials of the omics data-intensive research for science and society. Additionally, I discuss the need to communicate uncertainty as a fundamental construct and intrinsic part of postgenomics personalized medicine, not to forget the gaps regarding the lack of adequate governance, and issues over providing a proper nutritional education to athletes as onus of the international sports organizations. “Let food be your medicine, and medicine be your food” Hippocrates